A Framework for Assessing Knowledge Transfer Between Learners and Instructor Through Externalization Process - Suebsom, Korawan (2010)
Knowledge transfer is important in the educational system. Most universities emphasize the effectiveness of knowledge transfer from the instructors to learners since the effectiveness of knowledge transfer can improve teaching methods. In the process of knowledge transfer from the instructors and learners, the three key characteristics of knowledge, knowledge ambiguity, knowledge disruption and knowledge distribution can cause problems in the knowledge transfer and thus affect the externalization of learners. This study is aimed in constructing a framework for assessing the knowledge transfer, by way of online learning, from the instructors to the learners and to examine the three key characteristics of knowledge and their relationship with the transfer process and the learning outcomes. The study used a mixed method design using the data collected from three universities in Southern Thailand. The data was analyzed using descriptive statistics and multiple regressions. The study too used the qualitative design for content analysis of the data collected from weblogs. The data was analyzed to determine the knowledge that learners gained and also the learners' reflection of the knowledge transfer. Using this analysis the effectiveness of online instructions from the instructors to learners was determined. The research findings revealed some significant results involving the three key characteristics of knowledge. The knowledge of learners was explained by 21.5 percent of knowledge ambiguity. In addition, 40.3 percent of perceived knowledge was explained by knowledge distribution. Finally, 41.3 percent was explained the learners' satisfaction when using tools and teaching techniques for knowledge distribution. The three key characteristics of knowledge together were, therefore, able to explain 64.3 percent of the learning outcomes, There are major important implications, for theory, as developed from this study: (1) A framework for assessing knowledge transfer can contribute much to the instructors and learners in knowing what knowledge that the instructors can transfer to learners and what knowledge is gained by the learners. This framework is useful for the instructors in their evaluation of knowledge transfer by learners. The knowledge can be transferred through online learning from the instructors to learners using methods and tools that are appropriate for knowledge transfer. (2) The knowledge gained is influenced by knowledge ambiguity. It is hoped that the instructor or instructors first of all find the appropriate methodology, in their efforts, to transfer knowledge to learners in the classroom and thus improve or make clear the knowledge before the transfer occurs. (3) A strong predictor of learners' behavior is knowledge disruption and as such it would be useful for the instructors to know the behavior of learners when using technology as a tool in transferring knowledge. (4) Another strong predictor for perceiving knowledge is knowledge distribution. The instructors need to know the prior knowledge of learners by testing the level of knowledge of the learners, whether it is low, medium or high before selecting the right methods to transfer knowledge. (5) Learners' satisfaction of tools and teaching techniques are also influenced by knowledge distribution. The instructors need to create information details which are suitable for the course. The study suggests that the instructors should allow learners time to study and use a program. In addition, the feedback of learners from weblogs do tell the instructors what the learners think of the knowledge transfer process, and what knowledge that can be externalized into documents from the process of knowledge transfer between the instructors and learners.